Effects of Harvesting Age of "Pisang Ambon Jepang " (Musa cavendishii Lambert) to The Rate of Ripening - Indra Neffi Ridwan (Warta Industri Hasil Pertanian, 1989)
The aim of this experiment is to study the effect of harvesting age of "Pisang Ambon Jepang (Musa cavendishii Lambert) to the rate of rip g ening. The fruit age was varied from 3.5 to 4.5 months. The ripening process was induced by moisteninin dilute ethrel of 720 ppm and calcium carbide of 0.6%. The analysis was carried out soon after seven days of the ripening process. The results showed that the suitable fruit age was between 4 and 4.5 months.